Depressive symptoms and their relation to age and chronic diseases among middle-aged and older adults in rural South Africa - Geldsetzer, Pascal; Bärnighausen, Till (The journals of gerontology. Series A, Biological sciences, medical sciences, 2019)
AbstractBackground. Understanding how depression is associated with chronic conditions and sociodemographic characteristics can inform the design and effective